(untitled) (Journal of Scientific Research, 2010)
Opto-electronic properties of three new carbazole based co-polymers were investigated. The decay kinetics of triplet emission of the co-polymers was observed. Several findings such as optical band-gap, singlet to singlet transition energies, triplet to singlet transition energies, exchange energies (?EST) have been presented. In comparison to the other material carbazole-oxadiazole based polymer with OMe, P1, H21C10, P2 and H12C10O, P3 exchange energy is below 0.5 eV and triplet energy is significantly higher. The energy gaps between singlet and triplet excited states are 0.44-0.47 eV. From decay kinetics the triplet excited state life-times were found to be several orders of ms at 10-13 K that reduces to less than 3 ms at room temperature. Keywords: Time resolved emission spectroscopy; Carbazole; Conjugated polymers. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.4666 J. Sci. Res. 3 (1), 13-24 (2011)